Influence of maxillary posterior dentoalveolar discrepancy on angulation of maxillary molars in individuals with skeletal open bite - Luis Ernesto Arriola-Guillén; Aron Aliaga-Del Castillo; Carlos Flores-Mir (SpringerOpen, 2016)
Abstract Background The aim of this study was to determine the effect of the maxillary posterior dentoalveolar discrepancy (MPDD) on the angulation of maxillary molars in open bite subjects. Methods Pre-treatment lateral cephalograms of 90 young adults with skeletal open bite were examined. The sample initially included six groups categorized according to MPDD condition (present or absent) and sagittal skeletal facial growth patterns (classes I, II, or III). Then, the sample was separated into two groups according to MPDD (present = 50, absent = 40). When the eruption of the maxillary third molar was apparently blocked by the presence of an erupted second molar, a MPDD was considered. Maxillary molar angulation was measured. Independent T test was performed to determine differences between the groups considering MPDD condition. Principal component analysis (PCA) and multivariate analysis (MANCOVA) test were also developed. Results A decreased molar angulation was found in all groups with MPDD (overall p < 0.001, class I-p < 0.001, class II-p < 0.001, and class III-p < 0.05). The maxillary first and second molars angulations were lower between approximately 7° and 14° in cases with posterior discrepancy. The PCA was used to reduce the number of initial cephalometric variables; thereafter, a MANCOVA test was applied. Significance was only found for MPDD (p < 0.001), APDI (p = 0.001), and ratio (A'6'/A'P') (p = 0.026) for maxillary first molar angulation and APDI (p = 0.011) and MPDD (p < 0.001) for maxillary second molar angulation. Conclusions The MPDD generates a major mesial displacement of the second and first molar roots with a concurrent simultaneous distal angulation of the associated crowns in individuals with skeletal open bite.